Quantitative sensory testing is feasible and is well-tolerated in patients with sickle cell disease following a vaso-occlusive episode - Bakshi, Nitya (J Pain Res, 2018)
INTRODUCTION: Sickle cell disease (SCD) is an inherited blood disorder characterized by abnormally shaped sickle cells. The hallmark of this disease is intermittent, painful vaso-occlusive episodes (VOE), but a subset of individuals with SCD experience chronic pain. The mechanism of transition to chronic pain is not well understood in SCD, but there is evidence of altered pain processing in individuals with SCD. The impact of VOE on pain sensitivity is not established. The objective of this study was to determine the feasibility and tolerability of quantitative sensory testing (QST) in SCD following a VOE to better understand the contribution of VOE to the development of chronic pain. METHODS: As part of a larger pain sensitivity study, pediatric patients with SCD were offered QST following a VOE-related Emergency Room visit or inpatient hospitalization. The feasibility of recruitment and completion of QST was measured, and tolerability of QST was determined using post-QST assessments of pain, and compared with measurements at steady state. RESULTS: Ten participants completed QST following a VOE. The median age was 16.5, and 60% were female. Overall, 10 of 16 (62.5%) patients approached for QST following VOE completed QST. This included 8 of 12 patients who had previously completed QST at steady state. There were no statistically significant differences in pain intensity and Gracely Box scores after QST following a VOE, when compared to steady-state QST. CONCLUSION: QST is feasible and is well-tolerated following a VOE in patients with SCD. Large prospective studies are needed to determine the impact of VOE on experimental pain sensitivity and must take into account all factors contributing to pain sensitivity.